In Vitro Antifungal Activity of Ibrexafungerp (SCY-078) Against Contemporary Blood Isolates From Medically Relevant Species of Candida: A European Study - Quindós, Guillermo; Miranda-Cadena, Katherine; San-Millán, Rosario; Borroto-Esoda, Katyna; Cantón, Emilia; Linares-Sicilia, María José; Hamprecht, Axel; Montesinos, Isabel; Tortorano, Anna Maria; Prigitano, Anna; Vidal-García, Matxalen; Marcos-Arias, Cristina; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Ibrexafungerp (SCY-078) is the newest oral and intravenous antifungal drug with broad activity, currently undergoing clinical trials for invasive candidiasis. Objective The aim of this study was to assess the in vitro activity of ibrexafungerp and comparators against a collection of 434 European blood isolates of Candida. Methods Ibrexafungerp, caspofungin, fluconazole, and micafungin minimum inhibitory concentrations (MICs) were collected from 12 European laboratories for 434 blood isolates, including 163 Candida albicans, 108 Candida parapsilosis, 60 Candida glabrata, 40 Candida tropicalis, 29 Candida krusei, 20 Candida orthopsilosis, 6 Candida guilliermondii, 2 Candida famata, 2 Candida lusitaniae, and 1 isolate each of Candida bracarensis, Candida catenulata, Candida dubliniensis, and Candida kefyr. MICs were determined by the EUCAST broth microdilution method, and isolates were classified according to recommended clinical breakpoints and epidemiological cutoffs. Additionally, 22 Candida auris from different clinical specimens were evaluated. Results Ibrexafungerp MICs ranged from 0.016 to ≥8 mg/L. The lowest ibrexafungerp MICs were observed for C. albicans (geometric MIC 0.062 mg/L, MIC range 0.016–0.5 mg/L) and the highest ibrexafungerp MICs were observed for C. tropicalis (geometric MIC 0.517 mg/L, MIC range 0.06–≥8 mg/L). Modal MICs/MIC50s (mg/L) against Candida spp. were 0.125/0.06 for C. albicans, 0.5/0.5 for C. parapsilosis, 0.25/0.25 for C. glabrata, 0.5/0.5 for C. tropicalis, 1/1 for C. krusei, 4/2 for C. orthopsilosis, and 0.5/0.5 for C. auris. Ibrexafungerp showed activity against fluconazole- and echinocandin-resistant isolates. If adopting wild-type upper limits, a non-wild-type phenotype for ibrexafungerp was only observed for 16/434 (3.7%) isolates: 11 (4.6%) C. parapsilosis, 4 (5%) C. glabrata, and 1 (2.5%) C. tropicalis. Conclusion Ibrexafungerp showed a potent in vitro activity against Candida.